Antioxidant Activities and FT-IR of Azanza garckeana Leaves Extracts - Magaji, Peace Asaph; Muhammad, Aminu; Shadrach, Philip (African Journal of Biochemistry and Molecular Biology Research, 2024)
The objective of this study is to eval_uate the antioxidant activities of three extracts of Azanza garckeana leaves. Azanza garckeana fruits, seeds and roots have been reported to cure cough, liver disorders, abscess, diabetes, infertility and mental sickness. Natural antioxidants found in plants help to reduce oxidative stress in the body that lead to variety of health issues, including heart disease, diabetes, muscular degeneration, and cancer. The antioxidant activities of Azanza garckeana leaves extracts were determined by 2,2-diphenyl-1-picryhydrazyl (DPPH) and Ferric reducing antioxidant power (FRAP) Methods. Azanza garckeana leaves were extracted with three solvents of increasing polarity of n-hexane, ethyl acetate and methanol and their antioxidant properties were tested. DPPH results showed that methanol and ethyl acetate extracts have excellent antioxidant activities when compared with the standard oxalic acid. Methanol has the highest antioxidant activity, followed by ethyl acetate and then n-hexane extract with IC50 values of 1.17µg/ml, 2.23µg/ml and 17.83µg/ml, respectively. Ferric reducing antioxidant power also indicated that ethyl acetate and methanol extracts have higher reducing power than n-hexane extract when compared with ascorbic acid (AA). This may be as a result of higher concentrations of flavonoid and phenol in the extracts. The leaves extracts of Azanza garckeana contains potent antioxidant agents supporting its folkloric uses in the treatment of diseases.